Teaching History in the Age of Globalization: Reconciliation in History Teaching in Germany and France and its Implications for Vietnamese and French - Phạm, Tung Hồng (VNU Journal of Science: Social Sciences and Humanities, 2015)
At the beginning of the 21 st century, as the human kind just entered the age of globalization, a “history textbook crisis” broke out in East Asia. In fact, the differences in teaching history have existed in all parts of the world and become a source of new hostilities, conflicts and wars among peoples. Being ware of this, German and French educators and historians have tried in different ways to reconcile the past and finally found out the resolution in compiling a common history textbook using in the two countries since 2006. This can be a good example for Vietnamese and French educators and historians in their effort to settle the colonial past and help the younger generation of the two nations in building common better future. These are the aim and contents of this paper.